Exopolysaccharides from camel milk-derived Limosilactobacillus reuteri C66: Structural characterization, bioactive and rheological properties for food applications - A.K.M. Humayun Kober; Mohamed Abdin; Athira Subhash; Shao-Quan Liu; Enes Dertli; Basim Abu-Jdayil; Pau-Loke Show; Mutamed Ayyash (Food Chemistry: X)
Microbial exopolysaccharides (EPS) are valued as safe, functional bio-ingredients in food. Produced by microorganisms like lactic acid bacteria (LAB), they enhance the rheological and sensory properties of food products. In this study, Limosilactobacillus reuteri C66 (EPS-C66), was utilized to produce EPS. EPS-C66 was isolated, purified, and characterized for its rheological properties and biofunctionalities. Molecular weight was 3.7 × 105 Da. Three monosaccharides (arabinose, mannose, and glucose) were identified. At 10 mg/mL, EPS-C66 exhibited significant scavenging activity against DPPH and ABTS radicals, achieving 67.9 % and 31.3 %, respectively. Additionally, it reduced the viability of Caco-2 and MCF-7 cancer cells by 93.7 % and 61.4 %, respectively. EPS-C66 also demonstrated antibacterial effects against S. aureus, S. typhimurium, L. monocytogenes, and E. coli, with ranges of 5.9, 6.1, 6.0, and 5.7 log CFU/mL, respectively. The current study highlights that EPS-C66 can enhance the health benefits and rheological properties of foods, contributing to the development of novel functional foods.